2014
DOI: 10.1037/a0033509
|View full text |Cite
|
Sign up to set email alerts
|

Relative influences: Patterns of HPA axis concordance during triadic family interaction.

Abstract: Objective Within-family concordance in physiology may have implications for family system functioning and for individual health outcomes. Here, we examine patterns of association in cortisol within family triads. Methods A total of 103 adolescents and their parents sampled saliva at multiple timepoints before and after a conflict discussion task. We explored whether within-family associations existed and were moderated by stepparent presence and youth gender, and whether within-family patterns of influence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
81
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 24 publications
7
81
3
Order By: Relevance
“…The current findings contrast with Saxbe et al (2014), in that fathers’ cortisol patterns predicted mothers’ cortisol. Specifically, when fathers had high cortisol levels when beginning the laboratory challenge, their wives had high cortisol levels at the end of the family interaction.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current findings contrast with Saxbe et al (2014), in that fathers’ cortisol patterns predicted mothers’ cortisol. Specifically, when fathers had high cortisol levels when beginning the laboratory challenge, their wives had high cortisol levels at the end of the family interaction.…”
Section: Discussioncontrasting
confidence: 99%
“…Up to the present, what research exists on child cortisol and family dynamics has focused mainly on insider perspectives (i.e., self-report) of early and current family functioning, and few have examined cortisol levels from both parents during a task (Saxbe, Margolin, Shapiro, Ramos, Rodriguez, & Iturralde, 2014; Stenius, Theorell, Lilja, Scheynius, Alm et al, 2008). Moreover, no study has investigated linkages between parent cortisol response and children’s adjustment to normative developmental change.…”
mentioning
confidence: 99%
“…One study reported non-significant findings for a composite of multiple indices (Bloch, Haase, & Levenson, 2014) and another found non-significant results for HR and EDA (Reed et al, 2013). Eleven studies used laboratory-based discussions tasks (e.g., Laurent & Powers, 2007; Saxbe et al, 2014); the majority of these tasks involved engaging in conflict or problem solving. Seven studies tested linkage in the home environment; all of these measured endocrine system markers (e.g., cortisol; Saxbe & Repetti, 2010; Storey et al, 2000), except for one study that examined linkage in sleep timing (Hasler & Troxel, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon, known as physiological linkage, synchrony, or coregulation, is defined as covariation between two people in their physiological states. Although documented as early as the 1950s in client-therapist dyads (Di Mascio, Boyd, Greenblat, & Solomon, 1955), interest in physiological linkage, especially in romantic couples, has been increasing in the past few years (Helm, Sbarra, & Ferrer, 2012, 2014; Liu, Rovine, Cousino Klein, Almeida, 2013; Papp, Pendry, Simon, & Adam, 2013; Saxbe et al, 2014; Saxbe & Repetti, 2010). The advent of more sophisticated technological and quantitative techniques for capturing dynamic inter-individual physiological processes (Ferrer & Helm, 2013; McAssey, Helm, Hsieh, Sbarra, & Ferrer, 2013; Poh, Swensen, & Picard, 2010) has primed the field for continuing advances.…”
mentioning
confidence: 99%
“…For example, positive associations between mothers’ and children’s cortisol levels have been reported in a variety of studies (Granger et al, 1998; Hibel et al, 2009; Papp et al, 2009). Although the literature examining covariation with couples is small, studies have consistently reported positive correlations between partners’ cortisol levels, both in the laboratory (e.g., Laws et al, 2015; Saxbe et al, 2014) and in momentary studies conducted over several days (Saxbe and Repetti, 2010; Liu et al, 2013; Papp et al, 2013). The implications of cortisol covariation are complex (Timmons, Margolin, & Saxbe, 2015).…”
mentioning
confidence: 99%